Analysis Of Errors In The Use Of Sentences In Anecdote Texts Via Comic Strip Media Class X Students Of TSE (Tourism Services Enterprise) SMK Negeri 3 Balikpapan Academic Year 2023/2024 - Prasetya, Kiftian Hady; Kumalasari, Enggar; Maulida, Nurliani; Ramadania, Dhea Fitriana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This research aims to determine the location of language errors in writing anecdote texts in the use of appropriate sentences. The method used in this research is descriptive qualitative. The technique for analyzing sentence usage errors is carried out by giving assignments in the form of written texts to class X ULW (Tourism), Then the researcher took 5 samples to identify errors in the text presented in the comic strip. After identifying them, the researcher provided a description and explanation regarding errors in the use of sentences in the comic strip. Based on the results of this research, it shows that there are errors in the use of sentences in comic strips, namely in writing foreign languages, using capital letters, using punctuation, writing in spelling vocabulary, and choosing the right words.